(untitled) (Annual of the Faculty of Philosophy in Skopje, 2023)
Masculinity and femininity can both be freely defined through the spectrum of certain characteristics, points of view, features, expectations, and explanations linked to the behavioural traits of masculine and feminine individuals. Those are socially constructed dimensions that explain the male and female status, alongside the position of the sexes within societies. The aim of this study is to re-examine the extent to which culture and cultural context impact the shaping of male and female individuals, as well as the ways through which those influences take place. The relationships between the culturally established set of categories, such as those for gender identification in individuals, are referred to as “human taxonomy”, or “cultural classification”. Hence, the norms, regulations, stances, behaviours, conduct, and, ultimately, the expectations of individuals in a sociocultural environment greatly depend on the relations between mannature-culture. In that context, this paper elaborates on different socio-anthropological theoretic concepts revolving around the creation of masculinity and femininity while emphasizing the historical and contemporary d